The Effect of Student-Run Vision Screenings on Ophthalmic Education and Recognition of Visual Impairment - Justin Chin; Patrick J. O'Toole; Jun H. Lin; Julie M. Lavalliere; Narcisse Amine; Amanda Milam; Grace Huang; Mahnoor Asghar; Junsanto Bahri; Sonu Sahni (Shahid Beheshti University of Medical Sciences, 2018)
Objective: For many in the United States, standard health insurance does not cover eyecare, leading to lapses in care and exacerbations of pre-existing conditions. Touro College of Osteopathic Medicine (TouroCOM) recognizes the importance of ocular health and offers the opportunity to engage the community through student-run vision screenings. This study aims to assess the effect of medical student-run vision screenings in supplementing pre-clinical education and to review health fair data on common vision pathologies seen in Harlem, New York. Methods: Pre- and post-surveys were administered to medical student volunteers to assess their comfort in performing a basic vision screening. Training was given in regards to screening protocols and applied at health fairs. Results: 90% of medical students (n=20) indicated discomfort in performing a basic vision screening when solely relying on their preclinical coursework. In comparison, after a training session and use during a health fair, 100% (n=20) indicated that they were comfortable with performing a vision screening.  60% of health fair participants (n=193) met referral criteria in requiring further testing or follow-up care. 100% of participants had some degree of refractive error, with 6% (n=7) having concomitant color vision abnormality and 9% (n=11) with macular abnormalities. Conclusion: Osteopathic medical students are better equipped to perform basic vision screenings and recognize visual disease with additional training and practice at health fairs. This engagement allows for early clinical experience, osteopathic outreach, and interprofessionalism. Furthermore, this provides an opportunity for community members to receive information that may guide future health decisions.